Inovasi Akar Rumput Pengelolaan Hutan Adat: Studi Kasus Komunitas Kulawi-Marena di Kabupaten Sigi, Sulawesi Tengah - Wibowo, Ari; Palijama, Martje Leninda; Kutanegara, Pande Made; Cahyono, Eko; Tillah, Mardha (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2021)
The Kulawi-Marena community is one of the communities with customary law units located in Sigi Regency, Central Sulawesi.They have inhabited the area around the forests of the Lore Lindu National Park (TNLL) long before Indonesia became a country. The Katuvua customary law system is a mechanism for effective natural resource management in preserving forests and ensuring social order, rather than the governance applied by national park managers. The writing of this article is based on research conducted by the author with the Indonesian Institute for Forest and Environment (RMI) with the support of FAO funds in 2018. Qualitative methods were used in the data collection process through Participatory Rural Appraisal (PRA), in-depth interviews, and Focus Group Discussions (FGD). This article describes the customary forest management practices by the Kulawi-Marena community based on the Katuvua customary law system. Furthermore, this article shows that this practice is a form of grassroots institutional innovation that reflects